2019
DOI: 10.4070/kcj.2019.0074
|View full text |Cite
|
Sign up to set email alerts
|

The Current Status of Intervention for Intermediate Coronary Stenosis in the Korean Percutaneous Coronary Intervention (K-PCI) Registry

Abstract: Background and objectives: Intermediate coronary lesion that can be under-or overestimated by visual estimation frequently results in stenting of functionally nonsignificant lesions or deferral of percutaneous coronary intervention (PCI) of significant lesions inappropriately. We evaluated current status of PCI for intermediate lesions from a standardized database in Korea. Methods: We analyzed the Korean percutaneous coronary intervention (K-PCI) registry data which collected a standardized PCI database of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
(39 reference statements)
1
5
2
Order By: Relevance
“…Notably, the indication for PCI did not seem to differ between SB-PCI and MV-PCI, as the incidence of pre-PCI evaluation, including stress-testing or coronary computed tomography angiography, did not differ between the two groups. The frequency of invasive fractional flow reserve measurement in the SB-PCI group (16%) was higher than that reported in other nationwide registries (4.0% in 2017 for the United States [4] , 11.5% in 2014 for South Korea [13] , 6.8% in 2014 for Spain [14] , and 3.3% in 2010–2013 for Germany [15] ). SB-PCI with less frequent use of DES was not associated with an increase in immediate procedure-related complications ( Fig.…”
Section: Discussioncontrasting
confidence: 57%
“…Notably, the indication for PCI did not seem to differ between SB-PCI and MV-PCI, as the incidence of pre-PCI evaluation, including stress-testing or coronary computed tomography angiography, did not differ between the two groups. The frequency of invasive fractional flow reserve measurement in the SB-PCI group (16%) was higher than that reported in other nationwide registries (4.0% in 2017 for the United States [4] , 11.5% in 2014 for South Korea [13] , 6.8% in 2014 for Spain [14] , and 3.3% in 2010–2013 for Germany [15] ). SB-PCI with less frequent use of DES was not associated with an increase in immediate procedure-related complications ( Fig.…”
Section: Discussioncontrasting
confidence: 57%
“…PCI devices including hemodynamic support devices, tools for image (intravascular ultrasound, optical coherence tomography and physiology (fractional flow reserve) in multivessel AMI and optimal medical therapy were advanced considerably compared with a decade ago. 4) Although previous clinical studies have demonstrated an inverse relationship between hospital PCI volume and in-hospital mortality in AMI patients, 5) current study did not show the mortality difference between high and low PCI volume centers.…”
contrasting
confidence: 67%
“…Over the years, IVUS is often used for the assessment of severity of coronary artery stenosis in real-world practice and has certain clinical value for risk stratification of intermediate coronary lesions [18,19]. Previous studies suggested that minimum lumen area <4.0 mm 2 , plaque burden >70%, and IVUS-derived thin-cap fibroatheroma (TCFA) may be predictive for future worse outcomes [20][21][22].…”
Section: Discussionmentioning
confidence: 99%